(untitled) (INTERNATIONAL JOURNAL OF INDUSTRIAL AND PRODUCTION ENGINEERING, 2025)
The study was undertaken to predict the seakeeping ability of a drillship at sea using a set of measured data retrieved from the ship. The study applied measured techniques and MATLAB program to predict the station keeping ability of a drillship with emphasis on wave estimate, true heading angle and generated wave motions. Findings from the study with respect to the research methodologies revealed disparities in wave height estimate, true heading angle estimate and regenerated wave in various ship motions using the measured value approach. Likewise, the drill ship speeds by transfer functions showed huge difference between the encounter domain and absolute domain as the drillship speed influences the heading accuracy of the ship, thus, resulting in various ship motions and degrees which alter the optimal station keeping ability of the drillship. In addition, the accuracy of the estimation of the peak period was revealed to be relatively high while the accuracy for the mean period and zero-up crossing period deviated from the true value. In general, the measured values were not reflections of the true heading state of a drillship, as there is need for incorporating more modified systems and simulations to better predict the ship keeping ability under various wave impacts at sea.